A importância da sala de recursos para incluir o aluno com especialidades: um estudo na Escola Municipal Professor Antônio Farias - Sousa, Joseane Gomes de (Universidade Federal do Tocantins, 2022)
This Course Conclusion Paper aims to analyze the importance of the multifunctional resource room to include students with special needs / disability / specialty in a school in the municipality of Tocantinópolis -TO. The type of research adopted is the Case Study, with a qualitative approach, having as instruments and techniques of data collection: the bibliographic survey; the application of a questionnaire to the class teacher; classroom observation; analysis of the activities developed (lesson plan) and documentary analysis. At the first moment we carried out research based on the legislation on Special Education, as well as texts that addressed the theme presented here. The second moment we had the field research, a study carried out in the Municipal School Professor Antonio Farias that attends children in the multifunctional resources room, with various specialties. Therefore, we selected the resource room, for the study, and to verify the types of specialties served in it, to identify the role of the resource room in the development of the teaching-learning process of the students. Therefore the results of the study show that the resource room has total importance in the lives of students with special needs both personal, social and mainly intellectual. Since it is through the activities carried out in class that their development and learning is acquired and improved.